34.1k views
3 votes
Solve please
ab - cd = 0
solve for C

2 Answers

4 votes

Answer:

c = ab / d

Explanation:

ab − cd = 0

Add -ab to both sides:

ab − cd+− ab= 0 +− ab

−cd=−ab

Divide both sides by -d:

− cd/−d = − ab /−d

c = ab / d

User Hourglasser
by
5.5k points
4 votes
c= ab/d


step by step:
1. isolate the term in C, ab=cd
2. divide both sides by the coefficient of c, which is d
ab/d = cd/d
3. the d’s cancel
ab/d=c
but to make it look nicer, c= ab/d. both answers are correct though!
User Brandon Black
by
5.3k points